WHAT ARE DEMANDING OPERATIONS IN SUBSEA WORK? - HÅVOLD, JON IVAR; Vederhus, Lillian; Nistad, Steinar (WIT Transactions on Engineering Sciences, 2018)
In recent years, offshore operations have changed from a focus on anchor handling and rigging to more subsea installation and IMR (inspection, maintenance, repair). Situations where large and heavy modules are placed on the seabed by increasingly specialized and bigger boats creates the potential for major accidents. To uncover the safety challenges of this new development, 14 semi-structured in-depth interviews were conducted covering a broad scope of experience and skills from subsea work (ROV operators, crane operators, captains/first/second mates, oil service and oil company operators). All interviewees claimed that moving the offshore oil operations from surface to subsea leads to more demanding operations and more complex and risky work situations. According to the informants, these developments mean that cooperation and communication are essential since the number of actors increases substantially and the units grow larger. This seems to place increased demands in understanding both culture, language, tools, potential events, possible preventative measures (including training) and handling when critical events occur. Demanding situations occur when customers push on weather limits and costs and there are fewer people at work. Other situations viewed to be demanding are when something is hoisted through splash zones, and the moment when heavy constructions are placed on the seabed template. It has been shown that simulation training can improve safety and be an important preventive safety measure.